Social representations of work by youngsters classified as intellectually disabled: a dialogic approach - Valdés Véliz, Marco A. (Revista de Psicología, 2012)
This paper exposes the social representations of work of youngsters who have been catalogued as intellectually disabled. They participated in a dual vocational training program in two special schools located in Santiago. The study adopts the social model of disability, linking concepts such as dialogic intelligence, educating city and critical pedagogy. Using a grounded theory design and a procedural approach, it describes the categories that shape the field of the representations that are being studied, identifying attitudes, conflicts and their sources of information and determination. Results are discussed regarding the educational curriculum, which is based in work internships. The conclusion states that participants build symbolizations of social reality that guide their daily experience.